Pengaruh Customer Relationship Management dan Tarif Terhadap Pengguna Transportasi Go-Jek Di Kota Bekasi - Matdio Siahaan; Ridwan Anwar; Indra Lubis (Jurnal Manajemen, 2020)
The Gojek phenomenon is becoming popular in Bekasi, due to the development of technology and information in the era of the industrial revolution 4.0, so that the public inevitably user transportation facilities that are increasingly developing, so that competition is very tight the company is trying to improve service and customer satisfaction. The purpose of this research is to be able to analyze the extent of CRM Segmentation with e-busniess (online) in Gojek Management, as well as Tariffs for Gojek User . This implementation is carried out by taking objects in the area of ​​Bekasi City, West Java Province. Research methods by collecting primary data with a Likert scale questionnaire level 5 scale and interviews with observations to the field. The results of this study are based on population and sample of 75 people, in 2019 showing 40% customer to usage of the go-jek to upgrade service to customer sothat business can run well.